Existence and uniqueness of an inverse problem for a wave equation with dynamic boundary condition - Tekin, Ibrahim (Isik University jaem@isikun.edu.tr, 2020)
In this paper, an initial boundary value problem for a wave equation with dynamic boundary condition is considered. Giving an additional condition, a time-dependent coefficient is determined and existence and uniqueness theorem for small times is proved. © Isik University, Department of Mathematics, 2020.
Keywords: Fourier method; Inverse problem; Wave equation